EXPLORING TRENDS IN SOCIAL SECURITY MANAGEMENT: A BIBLIOMETRIC REVIEW (Social Security Management Journal, 2024)
Social security systems worldwide encounter a range of challenges including poverty, inequality, pandemic-induced impacts, non-traditional employment, aging populations, and threats posed by the collaborative economy. These challenges call for various reforms that encompass private sector engagement, expenditure reduction, expanded coverage, improved management practices, decoupling benefits from employment, inclusion of local stakeholders, and support for self-employed workers. Implementing these reforms is imperative for safeguarding the well-being of vulnerable populations. The current bibliometric review aims to analyse research trends related to social security management. This review utilised ScientoPy and VOSviewer to comprehend the nature of collected datasets from Scopus and Web of Science (WoS) databases. The findings of this review revealed that the number of publications in both databases peaked in 2019, suggesting that previous studies continue to be interested in the current topic. The scholarly publication “Social Security Bulletin” is renowned for its extensive coverage of social security management research for empowering employees welfare. The keyword “social security” has significantly impacted the thematic content of scholarly social security management for the past three decades, from 1990 to 2023, as previous researchers have used it most frequently. Based on overlay visualisation mapping, the current review demonstrates that the terms "coverage," "social security legislation," and "atypical work," have been accorded greater significance since 2018. This study provides a thorough and worldwide perspective on the crucial subjects of social security management in order to empowerment of employees welfare. It is aimed at potential readers and researchers interested in better understanding these concepts and conducting more rigorous research on social security management.